Investigations in the Theory of Knowledge at the Maria Curie-Skłodowska University - Hetmański, Marek; Pomorski, Jan (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2025)
This collection consists of texts by four authors-Narcyz Łubnicki, Ludwik Fleck, Leon Koj, and Zdzisław Cackowski-who formed the first two generations of philosophy at the Marie Curie-Skłodowska University. They deal with the problems of human cognitive processes and activities, the structure of everyday and scientific knowledge, including its justification and normativity, extensional and intensional logic, semiotics and pragmatics, as well as the issue of human experience considered from the perspective of ethics and philosophical anthropology. The reader will learn about the history of the initiation and development of the science-oriented, anti-dogmatic, postulative method, and pragmatic directions of philosophical research conducted over half a century.